The guild book of the barbers and surgeons of York (British Library, Egerton MS 2572) study and edition - Wragg, Richard ca. 20./21. Jh (Health and healing in the Middle Ages, 2021)
A new exploration of the secular manuscripts and medieval medical texts associated with the York Guild and its members